Acid‐Sensitive BODIPY Dyes: Synthesis through Pd‐Catalyzed Direct C(sp3)−H Arylation and Photophysics. Issue 19 (15th March 2017) - Chong, Hui; Fron, Eduard; Liu, Zhen; Boodts, Stijn; Thomas, Joice; Harvey, Jeremy N.; Hofkens, Johan; Dehaen, Wim; Van der Auweraer, Mark; Smet, Mario
Abstract: A novel palladium‐catalyzed direct C(sp 3 )−H arylation of the methyl group at the 8‐position of BODIPY by bromoarenes was established. A deprotonative cross‐coupling process was supposed to be involved in the reaction. This approach allowed us to attach electron‐donating/withdrawing, halogen substituted aryls and a heteroaryl with a yield running from 55 to 99 %. Novel pH sensors, which in the absence of acid showed the occurrence of photoinduced electron transfer, were synthesized by attaching dimethylaniline to the methyl at the C8‐position of BODIPY. The reference compounds with dimethylaniline directly attached to the C8‐position were also synthesized and besides photoinduced electron transfer also showed a charge‐transfer emission. Their photophysical properties were investigated by steady‐state fluorescence, time‐correlated single‐photon counting and femtosecond fluorescence up‐conversion. Time‐dependent density functional (TD‐DFT) electronic‐structure calculations on the properties of the excited states corresponding to local excitation of the BODIPY core and to charge transfer were conducted. Upon addition of trifluoroacetic acid in toluene and ethanol, the partial fluorescence intensity recovery was at least an order of magnitude more efficient with the newly synthesized sensors compared to the traditional reference sensors. The improved sensitivity of these novel BODIPY‐based pH sensors was attributed to less efficient proton‐coupled electron transfer of the protonated species. Abstract : The right direction : A new synthetic approach for palladium‐catalyzed direct C(sp 3 )−H arylation of BODIPY at the methyl of the C8 position is described (see scheme). The approach allowed the attachment of electron‐donating/‐withdrawing, halogen substituted aryls and a heteroaryl. Novel N, N ‐dimethylaniline‐bearing pH sensors were synthesized by using this strategy.